2020
DOI: 10.1111/ejh.13391
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating the role of ferritin in the diagnosis of adult secondary hemophagocytic lymphohistiocytosis

Abstract: Background The standard diagnostic criteria for hemophagocytic lymphohistiocytosis (HLH) include hyperferritinemia to >500 ng/mL. This ferritin threshold is based on pediatric data, and evidence for its application among adults with secondary HLH is lacking. Objective and Methods We conducted a retrospective study assessing the relationship between extreme hyperferritinemia and adult secondary HLH at our institution. All adult inpatients seen over a 10‐year period, with serum ferritin >5000 ng/mL, were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…In terms of diagnosis, a prospective cohort study confirmed that HLH‐2004 criteria may be a beneficial instrument for early diagnosis of adult HLH 16 . However, studies have also shown that hyperferritinemia is not specific for adult or paediatric HLH and the value ferritin levels used in diagnostic criteria for adult HLH are too low to be clinically relevant 17,18 . In terms of the prognosis of the disease, investigations have been made to explore the relationship between ferritin and survival in patients with HLH, 19,20 Lin et al discovered that compared with a paediatric patient with ferritin decrease < 50%, a paediatric patient with a higher ferritin decrease (>95%) has an increased chance of survivour (17‐fold) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnosis, a prospective cohort study confirmed that HLH‐2004 criteria may be a beneficial instrument for early diagnosis of adult HLH 16 . However, studies have also shown that hyperferritinemia is not specific for adult or paediatric HLH and the value ferritin levels used in diagnostic criteria for adult HLH are too low to be clinically relevant 17,18 . In terms of the prognosis of the disease, investigations have been made to explore the relationship between ferritin and survival in patients with HLH, 19,20 Lin et al discovered that compared with a paediatric patient with ferritin decrease < 50%, a paediatric patient with a higher ferritin decrease (>95%) has an increased chance of survivour (17‐fold) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…At the time of 2004 criteria set up, serum ferritin > 500 ng/mL had a sensitivity of 84 % with no documented specificity [ 7 ]. In adults, ferritin levels ≥ 3000 μg/L are not predictive of HLH, whereas, in the pediatric population levels ≥ 10,000 μg/L are 90 % sensitive and 96 % specific [ 7 ]. In adults, there is no established upper limit for ferritin that is specific for HLH [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, ferritin levels ≥ 3000 μg/L are not predictive of HLH, whereas, in the pediatric population levels ≥ 10,000 μg/L are 90 % sensitive and 96 % specific [ 7 ]. In adults, there is no established upper limit for ferritin that is specific for HLH [ 7 , 8 ]. In a recent retrospective study in 2019, they reviewed 1055 adult patients with serum ferritin > 5000 ng/mL for HLH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations